Extending the feeding period beyond 8.0 mm of subcutaneous fat reduces feed efficiency without improving meat colour and tenderness of non-implanted feedlot steers - Zurbriggen, Gabriel Alberto; Maglietti, Carlos Sebastian; Pouzo, Laura Beatriz; Testa, Maria Laura; Riffel, Sebastián L.; Elizalde, Juan Carlos; Pavan, Enrique (Polish Academy of Sciences, 2022)
The effect of extending the pen-feeding period of non-implanted feedlot steers beyond the 8.0 mm fat thickness (FT) endpoint on performance, carcass and meat traits was evaluated. Sixty-four medium-sized British steers (308 ± 26 kg) were grouped into four blocks by weight and housed in 16 pens. Pens within each block were assigned to one of four finishing periods: 64, 91, 119 and 147 days on feed (DOF). The first harvest (64 DOF) was defined as the projected days to attain 8.0 mm FT. From the 8.0–13.8 mm FT endpoints (64 and 147 DOF, respectively), daily shrunk body weight (SBW) feed conversion increased from 9.98 to 15.76 kg/kg (P < 0.001), while daily carcass weight (CW) feed conversion increased from 15.34 to 18.27 kg/kg (P < 0.001). Carcass transfer (CW gain to SBW gain ratio) increased from 0.67 to 0.86 kg/kg. FT and marbling score increased at increasing rates during the finishing period (P < 0.001), whereas rib eye area increased at decreasing rates (P < 0.001). Extending the feeding period tended to improve meat tenderness at three days of ageing (P = 0.066), while there was no response at 14 days of ageing (P > 0.10). Overall, the 8.0 mm FT endpoint for non-implanted steers corresponded to proper performance and adequate meat quality.